Moderasi Beragama Kaum Milenial: Studi Pemikiran Habib Husein Ja’far Al-Hadar - Riska Mailinda; Arjuna Arjuna; Putri Regina Patricia; Heni Indrayani; Muhammad Ghazali (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2022)
The study was intended to discuss millennial religious moderations according to Habib Husein Ja 'Far Al-Hadar. The study is a qualitative study using descriptive methods. When it comes to data, it is a qualitative study with the method of library research, so the data used are books directly related to the study. The study sought to review Habib Husein Ja’far Al-Hadar's ideas about religious moderations of the millennials. It was concluded that Habib Husein Ja’far Al-Hadar's idea of religious moderation was essential in view of the many threats of radicalism against the millennials. The study recommends to religious institutions to apply religious moderations to millennials.